Numerical study on stability of composite cutter bar milling system in rotating coordinate frame. Issue 10 (11th August 2022) - Zhang, Yuhuan; Ren, Yongsheng; Zhang, Jinfeng
Abstract: This paper studies the chatter stability of composite cutter bar milling system in rotating coordinate frame. The main contribution of this paper is establishing a continuous distributed chatter analysis model for a composite cutter bar milling system in rotating coordinate frame. The stability of the milling system with a rotary symmetric dynamic cutter bar is predicted using the semi‐discrete time domain method. The effects such as internal damping, external damping, and symmetrical and asymmetric laminates on the stability of the milling system were analysed, and the results were compared between rotating and fixed coordinate frames. The results are consistent for symmetrical cutter bars in both the rotating and fixed coordinate frames. A new chatter instability zone appears at high rotating speeds due to the material internal damping of the rotating composite cutter bar.